REALIZE NAZHIR PROFESSIONALITY IN MANAGING MORE PRODUCTIVE WAKAF ASSETS - Faisal, Faisal; Nursariani, Nursariani (NOMOI Law Review, 2025)
The development of waqf assets cannot be separated from the role of the Waqf Nazhir . Although the Nazhir is not the only party who can determine the success or failure of waqf asset management, the role of the Nazhir is very central in the development of waqf assets.The legality of Nazhir as a party that manages and develops waqf assets has been clearly regulated in Law Number 41 of 2004, Government Regulation Number 42 of 2006 which has been amended to PP No. 25 of 2018, as well as various regulations of the Indonesian Waqf Board / BWI .Although various regulations governing the nazhir (trustee), the expertise of the nazhir remains a crucial issue in waqf management in Indonesia. The professionalism of the nazhir is key to ensuring that waqf assets do not simply languish but grow productively for the benefit of the community.